Telecommuting Intensity in the Context of COVID-19 Pandemic: Job Performance and Work-Life Balance - Alfanza, Ma. Theresa (Economics and Business, 2021)
The COVID-19 pandemic caused a prolonged and intensified telecommuting arrangement that raised a number of unprecedented concerns regarding its implications on employees’ job performance (JP) and work-life balance (WLB). This study primarily aimed at determining the relationship between telecommuting intensity and employees’ JP and WLB. Further, it sought to know if there was a significant difference in employees’ productivity when working at the office and at home. Lastly, it assessed whether previous frameworks on JP and WLB were still valid during the COVID-19 crisis.